ALIRAN ESSENSIALISME DAN REKONSTRUKSIONISME SOSIAL DALAM FILSAFAT PENDIDIKAN - Pratama, Aufar Rifqi; Nursikin, Mukh (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research examines two important currents in educational philosophy, namely essentialism and social reconstructionism. Essentialism emphasizes the importance of mastering basic knowledge and skills, while social reconstructionism focuses on the role of education in reforming society. The aim of this research is to analyze the differences and similarities between the two schools, as well as their implications for contemporary educational practice. The method used is a literature study with a comparative analysis approach. The research results show that although the two schools have fundamental differences in educational goals, they both emphasize the importance of the role of teachers and a structured curriculum. Essentialism tends to maintain the status quo, while social reconstructionism seeks to encourage social change through education. This research concludes that a synthesis of the two streams can provide a more comprehensive framework for facing educational challenges in the modern era.